Challenges for ice-associated top trophic Arctic animals in a changing climate - Hamilton, Charmain Danielle (UiT The Arctic University of Norway, 2017)
The papers of this thesis are not available in Munin. Paper I: Hamilton, C. D., Lydersen, C., Ims, R. A., Kovacs, K. M.: “Predictions replaced by facts: a keystone species’ behavioural responses to declining arctic sea-ice”. Available in Biol. Lett. 2015, 11:20150803. Paper II: Hamilton, C. D., Lydersen, C., Ims, R. A., Kovacs, K. M.: “Coastal habitat use by ringed seals Pusa hispida following a regional sea-ice collapse: importance of glacial refugia in a changing Arctic”. Available in Mar. Ecol. Prog. Ser. 2016, 545:261-277. Paper III: Hamilton, C. D., Kovacs, K. M., Ims, R. A., Aars, J., Lydersen, C.: "An Arctic predator-prey system in flux: climate change impacts on coastal space use by polar bears and ringed seals." (Manuscript). Published version available in J. Anim. Ecol. 2017, 86(5):1054–1064. Paper IV: Hamilton, C. D., Kovacs, K. M., Ims, R. A., Aars, J., Strøm, H., Lydersen, C.: "An Arctic predator, prey and scavenger system in a changing climate". (Manuscript). Published version with title "Spatial overlap among an Arctic predator, prey and scavenger in the marginal ice zone" available in Mar. Ecol. Prog. Ser. 2017, 573:45-59. The Arctic is currently in a rapid state of change, with temperature increases in this region being three times the rate of the global average and sea-ice extent declining rapidly. In 2006, a sudden shift in the sea-ice regime in Svalbard, Norway, occurred with the altered sea-ice conditions persisting to the present day. In order to study the impacts of the environmental changes occurring in the Svalbard region, the movement patterns, behaviour and degree of spatial overlap for ringed seals (Pusa hisapida, n=60), polar bears (Ursus maritimus, n=160) and ivory gulls (Pagophila eburnea, n=40) were investigated using data from biotelemetry devices equipped on these species before (2002-2004; ringed seals and polar bears) and after (2010-2013; all three species) the shift in the sea-ice regime occurred. These three species are trophically linked; ringed seals are the primary ...